1990
DOI: 10.1056/nejm199009273231302
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Biosynthetic Defects in Women with Late-Onset Congenital Adrenal Hyperplasia

Abstract: About one third of Israeli Jewish women with hirsutism, menstrual disorders, or unexplained infertility had nonclassic congenital adrenal hyperplasia. Secondary adrenal biosynthetic defects were frequent in these women and were probably caused by intra-adrenal androgen excess rather than by dual inherited enzymatic deficiencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
1
10

Year Published

1992
1992
2005
2005

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(42 citation statements)
references
References 33 publications
2
29
1
10
Order By: Relevance
“…A combined alteration of 21-hydroxylase and 11b-hydroxylase was observed in 7 cases. Apart from anecdotal records with evidence for an actual deficiency of these two enzymes (42), such findings have already been observed for patients with hyperandrogenism (23,24,43). The increased peak 21-DF levels displayed by 7 patients with high post-stimulation S/F ratios is difficult to reconcile with adrenal steroidogenesis.…”
Section: Figurementioning
confidence: 97%
See 1 more Smart Citation
“…A combined alteration of 21-hydroxylase and 11b-hydroxylase was observed in 7 cases. Apart from anecdotal records with evidence for an actual deficiency of these two enzymes (42), such findings have already been observed for patients with hyperandrogenism (23,24,43). The increased peak 21-DF levels displayed by 7 patients with high post-stimulation S/F ratios is difficult to reconcile with adrenal steroidogenesis.…”
Section: Figurementioning
confidence: 97%
“…Poststimulated 21-DF levels over 2.2 nmol/l were taken as indicative of 21-hydroxylase impairment (20,21). A post-stimulative S/F ratio above 0.12 was taken as indicative of an altered 11b-hydroxylase activity; this cut-off value was determined from previously published studies (12,(23)(24)(25). Similarly, it was assumed that 17,20-lyase was impaired when the 17-OHG/DHEA ratio and the 17-OHP/D4-A ratio after stimulation were above 3.0 (26)(27)(28)(29)(30).…”
Section: Endocrine Assessmentmentioning
confidence: 99%
“…Increased secretion of 17-hydroxyprogesterone after stimulation with ACTHhas been described in 30-71% of adrenal "incidentaloma", suggesting a defect in the 2 1 -hydroxylase gene (7,8). An exaggerated response of 17-hydroxyprogesterone to ACTHmay be due to mild 21-hydroxylase deficiency (9) or may be caused by other abnormalities of steroid biosynthesis in these tumors, such as 1 1(3-hydroxylase deficiency (10). The ratio of 1 1-deoxycortisol to cortisol is higher in 40% of patients with adrenal "incidentalomas", and these patients have increased responses of precursors of the mineralcorticoid and glucocorticoid pathway including 1 7-hydroxyprogesterone after stimulation with ACTH(ll).…”
Section: Discussionmentioning
confidence: 99%
“…But, at least to our knowledge, so far no mutation has been identified in the CYPIIB1 gene of individuals with LOCAH due to 11b-OH deficiency. The prevalence of 11b-OH deficiency has been reported to be between 0.8 and 8% in different studies carried out in women with hirsutism or hyperandrogenism (38,39). Carmina (37) recently found that only 0.6% of the hirsute women had LO 11b-OH deficiency.…”
Section: Discussionmentioning
confidence: 99%